SANCTIONS FOR THE RETURN OF STATE FINANCES BY CORPORATIONS IN THE SYSTEM OF CORRUPTION JUSTICE SYSTEM - Sаleh; Nurjaya, I Nyoman; Herman Suryokumoro; Setiawan Noerdjasakti; Zana Zerlina (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Corruption has become a serious problem that harms state finances and hampers development. The purpose of this study is to examine the provisions of Article 20 paragraph (7) jo. Article 18 paragraph (1) of Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption. This research uses several approaches including a statutory approach and a case approach. The results showed that the regulation regarding the sanction of returning state financial losses in corruption cases by corporations is still sectorally scattered, starting from Law Number 8 of 1981 concerning Criminal Procedure, Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption, Circular Letter of the Attorney General of the Republic of Indonesia Number B-036/A/Ft.1/06/2009 regarding Corporations as Suspects / Defendants in Corruption Crimes, Regulation of the Attorney General of the Republic of Indonesia No. 028/A/JA/10/10/2009 concerning Corporations as Suspects / Defendants in Corruption Crimes: Per- 028/A/JA/10/2014 on Guidelines for Handling Criminal Cases with Corporate Legal Subjects, Supreme Court Regulation No. 13/2016 on Procedures for Handling Criminal Cases by Corporations.